Ecosystem Services at the Archipelago Sea Biosphere Reserve in Finland: A Visitor Perspective - Viirret Elina; Raatikainen Kaisa Johanna; Fagerholm Nora; Käyhkö Niina; Vihervaara Petteri (MDPI AG, 2022)
The United Nations Educational, Scientific and Cultural Organization’s (UNESCO’s) Biosphere Reserves aim to be flagships of sustainable landscapes. Many of them are important locations for tourism and leisure activities. We explored the perceptions of short-term visitors and summer residents on ecosystem services (ESs) tied to characteristic habitats of the Archipelago Sea Biosphere Reserve in Finland. During holiday season, we conducted structured on-field interviews with 74 Biosphere Reserve visitors. From these data, we gained information on the visitors’ appreciation of different ESs and the selected habitats. We also derived habitat-specific ES profiles. Excluding the reedbeds, most habitats were both highly valued and considered as important producers of the listed ESs. The derived ES profiles were partially overlapping and inclined towards appreciation of cultural services, and the importance of scenery was highlighted. Provisioning services were not particularly appreciated. We discovered several linkages among biodiversity, ESs, and recreational land uses. Certain habitats were found to be in need of protection under high recreational land-use pressure, but also potential synergies were found. Our method introduces an important socio-cultural perspective into the region’s land management that aims to find a balance between the protection of the Biosphere Reserve’s unique biodiversity and the need to support sustainable local livelihoods and tourism.